Molecular Docking Test of Procoagulant Compounds in Biwa Leaves (Eriobotrya japonica (Thunb.) Lindl.) Against Factor VIII Deficiency in The Genetic Disease Hemophilia-A - Rahudatul Putri; Zahratul Idami (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The treatment of Hemophilia A remains chalenging, primarily the risk of inhibitor development and the high cost of recombinant Factor VIII treatment, necessitating the development of adjuvant therapeutic agents to enhance its effectiveness. This situation necessitates innovation in the form of developing adjunctive therapeutic agents aimed at improving the effectiveness and outcomes of existing therapies. Methodology: To address this need, this study was designed using an in silico virtual screening method with PyRx software and AutoDock Vina. All stages were conducted computationally, followed by molecular docking simulations to map the interactions and binding affinities between candidate compounds and the predetermined molecular target, von Willebrand factor Domain A3, in order to identify the most promising candidate compounds. Findings: The study successfully identified two compounds, namely Kaempferol and Phenolic acid, which showed the strongest interaction and the best stability profile against the von Willebrand factor A3 domain. The binding free energy (ΔG) value for Kaempferol was -7.9 kcal/mol and for Phenolic acid -4.4 kcal/mol, with a stability value (RMSD) of 0.0 Å for both compounds. The affinity value of Kaempferol is better than that of the reference compound (Coumarin, ΔG = -5.9 kcal/mol), while Phenolic Acid shows a low value. This strong binding affinity indicates the potential of both compounds in stabilizing the interaction of Factor VIII with the A3 domain of von Willebrand factor, which can support hemostatic function. These findings concluded that Kaempferol and Phenolic Acid are worthy of further development as candidate adjunct therapies for Hemophilia A. Therefore, further studies are highly recommended to validate these findings through molecular dynamics simulations, in vitro and in vivo tests to confirm the biological activity and pharmacokinetic (ADME) profile of these compounds. Contribution: This study introduces the bioactive compounds Kaempferol and Phenolic acid from biwa leaves as new candidates for modulating the A3 domain of von Willebrand factor, offering a potential and largely unexplored adjunctive strategy in Hemophilia A treatment